Transformation of The Independent Curriculum: Strengthening the Islamic Dimension in Islamic Education - sahri sahri (Attanwir : Jurnal Keislaman dan Pendidikan, 2023)
The purpose of this study is to examine and analyze the implementation of the independent curriculum in the context of Islamic religious education with a focus on strengthening the Islamic dimension. type / research approach in the form of Library Research. Literature research is a research method carried out by collecting and analyzing various relevant literature sources, such as books, scientific journals, articles, and other documents, in order to answer research questions or gain a deeper understanding of a particular topic or issue. The results of the Independent Curriculum Transfomrasi research to strengthen the Islamic dimension in Islamic religious education, namely a). the concept and essence of the independent curriculum; b) The need to strengthen the Islamic dimension in Islamic religious education; c) Independent curriculum approach and strategy in Islamic religious education; d) implications and challenges in strengthening the Islamic dimension through the Merdeka Curriculum.